Peut-on apprendre à philosopher en ligne ? - Muriel Briançon (Centre National d'Enseignement à Distance, 2015)
In the digital era, are philosophy lectures still needed or can one learn to philosophize online? In 2013/2014, in the context of the course on "philosophy of education" for 3rd year students in educational sciences at the University of Aix-Marseille, we carried out a survey on their relation to philosophy. Two different groups were involved, the first one a 100% face-to-face unit, the second a 100% on-line unit. Learning philosophy online proved noticeably challenged by the representation the students have of philosophy. They feel both reluctant to use technologies and dependent on the physical presence of the trainer-philosopher, the professor whose presence does not just amount to giving a lecture. Moreover, the skills-based approach underlying online philosophizing raises the question of an ethical evaluation of the learning of philosophizing.